Penerapaan Model Student Facilitator and Explaining (SFE) dalam Pembelajaran PPKn Kelas XI di SMA Negeri 11 Semarang - Baehaqi, M. Lutfi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
The implementation of Pancasilan and Citizenship Education (PPKn) learning in schools still uses the old paradigm, namely implementing the Pancasila and Citizenship Education (PPKn) learning process in conventional ways, learning only focuses on the teacher. The purpose of this study was to find out the application of the student facilitator and explaining (SFE) model in Civics learning. This type of qualitative descriptive research. The results of the study show that the application of the SFE model: (1) can be applied to achieve all KD; (2) the steps taken by Civics teachers at SMA Negeri 11 Semarang are in accordance with existing regulations, starting from the teacher conveying KD to closing; (3) Obstacles and solutions in applying the student facilitator and explaining (SFE) model in Civics learning, namely the time required is relatively long, the solution to overcome this is by forming groups and then the facilities and infrastructure are less supportive, where not all classrooms have LCD projectors available, the solution the teacher gives assignments to make a schematic or concept map from paper and styrofoam.Keywords: Student Facilitator and Explaining (SFE), learning, PPKn